El autoestima y su influencia en el desarrollo socio afectivo de los niños (as) de los primeros años de educación básica de la escuela fiscal mixta vespertina Ing. Jorge Alex Serrano ubicada en el cantón El Guabo provincia de El Oro en el periodo lectivo 2012-2013. - Sol Macías, Yuli Alexandra (2013)
The family must inculcate the child in its earliest growth all values, beliefs and principles stage. It is important that legal representatives and teachers recognize and congratulate the child's accomplishments to contribute and develop their personality both socially and in the educational community.